Toward an objective measure of functional disability in dysferlinopathy. Issue 1 (23rd May 2015) - Woudt, Lisanne; Di Capua, Gabriella A.; Krahn, Martin; Castiglioni, Claudia; Hughes, Ricardo; Campero, Mario; Trangulao, Alejandra; González‐Hormazábal, Patricio; Godoy‐Herrera, Raúl; Lévy, Nicolas; Urtizberea, Jon Andoni; Jara, Lilian; et al.
ABSTRACT: Introduction: Understanding the natural history of dysferlinopathy is essential to design and quantify novel therapeutic protocols. Our aim in this study was to assess, clinically and functionally, a cohort of patients with dysferlinopathy, using validated scales. Methods: Thirty‐one patients with genetically confirmed dysferlinopathy were assessed using the motor function measure (MFM), Modified Rankin Scale (MRS), Muscle Research Council (MRC) scale, serum creatine kinase (CK) assessment, baseline spirometry data, and echocardiographic and electrophysiologic studies. Results: MFM and MRC scores showed a significant negative correlation with disease duration and inverse correlation with MRS, but not with onset age, clinical phenotype, or CK levels. Percent forced vital capacity (%FVC) correlated negatively with disease duration and onset age. Eight known pathogenic mutations were identified recurrently, 4 of which accounted for 79% of the total. Conclusions: The results suggest that MFM is a reliable outcome measure that may be useful for longitudinal follow‐up in dysferlinopathy. Recurrent mutations suggest a founder effect in the Chilean population. Muscle Nerve 53 : 49–57, 2016